Temporal trends of the utilization patterns of sedative-hypnotic medications in children, adolescents and young adults: a 21-year population-based study with joinpoint regression analysis - Carltin Chun Ting Kwok; Heidi Ka Ying Lo; Ching Yui Chan; Joe Kwun Nam Chan; Corine Sau Man Wong; Calvin Pak Wing Cheng; Chung Ho; Brian Man Ho Leung; Wilfred Shone Horn Wong; Zoe Hoi Shuen Yu; Edwin Ho Ming Lee; Wing Chung Chang (BMC Psychiatry)
Abstract Background There is limited research on real-world utilization patterns of benzodiazepines and Z-drugs (collectively-termed benzodiazepine-receptor agonists [BZRAs]) in children and adolescents, particularly in non-western countries. We aimed to examine temporal trends of BZRA prescribing-practice among children, adolescents and young adults in Hong Kong over a 21-year period. Methods This population-based study identified 60,660 individuals aged 4–24 years who had redeemed ≥ 1 BZRA prescription within 2000–2020, using data from medical-record database of Hong Kong public-healthcare-services. We calculated annual prescription prevalence (per 1,000 persons per year) for any BZRA, BZRA-subtypes (short- and long-acting benzodiazepines, Z-drugs) and individual BZRAs. Joinpoint-regression analyses were performed to assess temporal BZRA prescription trends, quantified by average annual-percent-change (AAPC), with 95% confidence-intervals (CIs). Results Overall BZRA prescription prevalence significantly increased (AAPC: 5.70% [95%CI: 5.31-6.54%]), from 1.88 in 2000 to 5.69 in 2020, uniformly across both sexes. Young adults (18–24 years-old) displayed the highest prescription prevalence, followed by adolescents (12–17 years-old) and children (4–11 years-old). Young adults and adolescents exhibited more pronounced increased BZRA use than children. Use of all BZRA subtypes consistently increased over time for all age-groups, except decline in Z-drug prescriptions in children. Lorazepam and diazepam represented the two most frequently-prescribed individual BZRAs, whereas alprazolam use showed the steepest increase. Anxiety and depression emerged as the most commonly-assigned diagnoses for BZRA-users. Conclusion This first Asian population-based study indicates a significant rising trend of BZRA prescriptions, especially among adolescents and young adults. Judicious prescribing-practices and further investigation clarifying factors contributing to increased BZRA use are warranted.